lncRNA SNHG14 Plays a Role in Sepsis-Induced Acute Kidney Injury by Regulating miR-93 - Shi, Chuanchuan; Zhao, Yuqian; Li, Qi; Li, Jianguo (Mediators of Inflammation, 2021)
Acute kidney injury (AKI) is a common organ injury in sepsis, which leads to poor prognosis. Long noncoding RNA (lncRNA) small nucleolus RNA host gene 14 (SNHG14) was recognized to induce cell injury in LPS-induced acute lung injury and Parkinson’s disease. We want to investigate the functions and mechanisms of SNHG14 in sepsis-induced AKI. Increased expression of SNHG14 was observed in LPS-induced HK-2 cells, and this was due to the activation of the TLR4/NF-κB pathway. In vitro studies showed that SNHG14 was involved in the oxidative stress, inflammation, and apoptosis of LPS-induced HK-2 cells. Further investigations confirmed that SNHG14 exerted the functions via miR-93 which could regulate the activation of NF-κB and STAT3 signaling by targeting IRAK4 and IL-6R. We also found that silencing SNHG14 also alleviated cellular injury processes of IL-1β and IL-6 in HK-2 cells via miR-93. We demonstrate that SNHG14 accelerates cellular injury in sepsis-induced AKI by activating IRAK4/NF-κB and IL-6R/STAT3 signaling via miR-93.